A The Management of Learning Innovation to Achieve The Quality of Graduates in SMK Negeri 1 Kuningan - Yulianti, Yulianti; Haryono, Haryono; Utanto, Yuli (Educational Management, 2018)
Vocational High School (SMK) as part of formal schools organized to prepare workforces that will compete and can fulfill job market demand. To achieve these goals it is necessary to innovate in learning process in order to create quality output. The purpose of this study is to identify and analyze: The type of learning innovation, the planning, the implementation, the evaluation, the constraints and solutions of learning innovation as an effort to achieve the quality of graduate in SMK Negeri 1 Kuningan. The method used in this research was descriptive qualitative. The data acquisition was done by in-depth interviews, participatory observation, and document study. The research result showed as follows: 1) The types of learning innovation arein the form of student-cantered learning, learning factory, learning using internet media, discovery and inquiry, problem based learning. 2) The planning of learning innovation includes making lesson plan, annual programs, semester programs, MGMP.3) The implementation of learning innovation includes initial activities, core activities, closing activities, 4) The evaluation of learning innovation includes process and result evaluation, 5) The constraints and solutions in innovating learning is some teachers have not fully master curriculum 2013, he solution that is carried out is by involving teachers in various trainings. Vocational High School (SMK) as part of formal school organized to prepare labor that will compete and can fulfill job market demand. To achieve these goals it is necessary to innovate in learning process in order to create quality output. The purpose of this study is to identify and analyze: The type of innovation learning, the planning, the implementation, the evaluation, the constraints and solutions of learning innovation as an effort to achieve the quality of graduate in SMK Negeri 1 Kuningan. The research result showed as follows: 1) The type of learning innovation among learning factory, student centered, Using peer tutors, cooperative learning, story telling, Discovery and inquiry learning, problem based learning. 2) The planning of learning innovation is at the beginning of the academic year by conducting various trainings such as, MGMP, In house Training, preparing learning tools, lesson plan, annual program, semester program. 3) The implementation of learning innovation by refer to the lesson plan that correspond to curriculum 2013. 4) Evaluation / assessment of learning process includes three aspects, there are: aspects of knowledge, skills and attitudes. 5) The constraints and solutions in innovating learning among some teachers who have not to understand how to implement the learning process by using curriculum 2013. The solution that has been done by the school is to follow the teachers in various training.